Discovery and inspection of documents under the Malaysian and English Civil Procedure: A Study on cases against the Internet Service Providers (ISPs) - Mohamed, Duryana (INSI Publications, 2012)
In civil procedure, parties are allowed to gather relevant documents before the trial. The parties may use any of the four methods namely, Discovery and Inspection of Documents, Interrogatories, Admission and Anton Piller Order. These methods are provided by the Rules of Court 2012 (Malaysia). While in the UK Civil Procedure Rules 1998 methods of gathering documents include depositions and exchange of witness statements. However, in choosing the most appropriate method the parties need to consider whether they are able to satisfy the requirements for method to be used. In discovery process, the plaintiff or the party needs to satisfy the court that the documents to be discovered are relevant and they are in the possession, custody or power of the opposite party. Meanwhile the opposite party is expected to comply with the court order for discovery by providing relevant documents or information. This paper attempts to discuss the process of discovery in Malaysia and United Kingdom by studying how the process works against the Internet Service Providers (ISPs) in both countries. The discussion will also include types of documents or information, which are discoverable and not discoverable from the ISPs and the effect of non compliance with the court order. For this purpose, the author will refer to the relevant laws, procedures and decided cases available in both countries.